KARAKTERISTIK IBU BERSALIN DENGAN SEKSIO SESAREA DI RUMAH SAKIT UMUM PUSAT HAJI ADAM MALIK MEDAN TAHUN 2015-2016 - Nadia Safira; Jemadi .; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
Seksio Sesarea is delivery by surgery on abdominal wall and uterine wall. At the central public hospital Haji Adam Malik Medan by 2015-2016, the proportion of mothers with seksio sesarea is 78%. The intention of this research is to determine the characteristics of maternity mothers with seksio sesarea at the central public hospital Haji Adam Malik Medan by 2015-2016. Research is descriptive with case series design.The study population was 521 of maternity mothers with seksio sesarea and 226 samples. And sampling was simple random sampling. Result showed the highest proportion of maternity mothers based on sociodemography are in the age group of 20-35 years (77,4%), Bataknese (56,2%), Islam (59,7%), housewife job (69,5%). Based on medico obstetrics factor on parity nullipara (41,6%), the length of maternity >2 years (72%), no history of disease(52,2%), kind of disease HIV (30,6%), birth history with seksio sesarea (50,8%), medical indication (100%), maternal disease (30,5%), abnormalities of baby (4,9%). There’s a history reference (57,5%), length of care >3 days (87,6%), not own expense (82,7%), return outpatient (97,3%). Statistical results with chi-square shows that there were no significant differences between length of care with history of disease (p=0,062) : parity (p=0,791). There were no significant differences between mothers age (p=0,740) with the length of maternity. There were no significant differences between history reference (p=0,504) with medical indication. There were significant differences between mothers age (p=0,001) with parity. Pregnant mothers are expected to check her health condition during pregnancy so that the illness is more quickly identified and get treatment according to the condition of pregnancy. Keywords : Seksio Sesarea, Mother, Characteristic